An initial investigation of nonsuicidal self-injury among male and female survivors of military sexual trauma. (October 2018) - Holliday, Ryan; Smith, Noelle B.; Monteith, Lindsey L.
Highlights: More than ¼ of military sexual trauma survivors endorsed nonsuicidal self-injury. Nonsuicidal self-injury was associated with more severe suicidal ideation. Nonsuicidal self-injury was also linked to PTSD symptoms and trauma cognitions. It is important to consider nonsuicidal self-injury in this population. Abstract: Nonsuicidal self-injury (NSSI) has been understudied among survivors of military sexual trauma (MST). The aims of the current study were to: (1) describe characteristics of NSSI among survivors of MST and (2) determine if MST survivors who have engaged in NSSI differ from those who have never engaged in NSSI in terms of the severity of posttraumatic stress disorder (PTSD) and depressive symptoms, trauma-related cognitions, and recent suicidal ideation. Participants were 107 veterans (65 females, 42 males) with a history of MST who completed measures of NSSI, PTSD and depressive symptoms, recent suicidal ideation, and trauma-related cognitions. Approximately one-fourth of participants ( n = 27; 25.23%) endorsed a history of NSSI. The majority of participants who engaged in NSSI reported that they first engaged in NSSI following MST ( n = 18; 66.67%). MST survivors with a history of NSSI reported more severe PTSD symptoms, recent suicidal ideation, and trauma-related cognitions. NSSI was relatively common in the sample and was associated with a more severe clinical presentation. Longitudinal research is needed to understand the development, maintenance, and function of NSSI in MST survivors, especially as it pertains to risk for suicidal self-directed violence.